DEVELOPING A TALENT SCOUTING INSTRUMENT FOR FENCING - Budi Santoso, Nuruddin Priya; Hidayatullah, M. Furqon (Universitas Negeri Semarang, 2016)
This research aimed to know indicators that could be utilized to develop an instrument to scout talent for fencing that fulfilled the criteria of being valid, reliable, objective and effective. The phases of this research and development study included (1) reviewing the criteria of a good test, (2) analyzing the sport to be tested, (3) literature review, (4) selecting test items, (5) establishing procedures, (6) peer review, (7) pilot study, (8) determining validity, reliability, and objectivity, (9) developing norms, (10) constructing test manual. The development of an instrument to scout talent for fencing contributed to (1) shortening the period of time needed to provide high achievement by means of selecting prospective athletes, (2) eliminating work and energy as well as separating high talent for the coach, (3) increasing the competitivity and number of athletes in order to achieve higher performance, (4) enhancing the athletes’ self-confidence, because the enhancement of athletes’ achievement is significant compared those of athletes of the same ages without experiencing any selection process, (5) making it easier for the coach to apply the test model for talent scouting for fencing in the field.